Simple educational intervention will improve the efficacy of routine antenatal ironsupplementation. - Senanayake, H M; Premarathne, S P; Palihawadana, T; Wijerathne, S (The Sri Lanka College of Obstetricians and Gynaecologists, 2010)
Aim: Sri Lanka has a policy of free provision of iron supplements to pregnant women. However, iron deficiency anemia remains common in pregnancy. Methods: We tested the hypothesis that educating women regarding improving bioavailability could improve the efficacy of iron supplementation. The education focused on how best supplements could be taken and on how they should be stored. We carried out a study using a quasi-experimental design on a group of women attending for antenatal care at a suburban University Obstetric Unit in Sri Lanka. The control group had care free of charge including iron supplementation and antihelminthic therapy. In addition, the study group received an education in small groups regarding maximizing bioavailability of iron. Hemoglobin and iron status of the women were compared between the groups at recruitment and at 34 weeks of gestation. Results: The two groups were equally matched in demographic data, and hemoglobin and iron status. There were significant differences between the two groups at 34 weeks in the hemoglobin levels, serum ferritin levels, anemia rates and the number with low ferritin (P < 0.0001 for all parameters), with a favorable outcome in the study group. The study group had used the iron tablets in ways that improved their bioavailability. Conclusion: A simple health education improved the efficacy of iron supplementation in this population. Such interventions should be an integral part of iron supplementation programs, especially in populations whose habits tend to reduce the bioavailability of iron.